A comunicação como vetor de sustentabilidade em parques nacionais: um estudo de caso sobre o Parque Nacional do Iguaçu - Machado, Rafael Rodrigues (2018)
It is observed that the quality and well-being of a population are directly related to the understanding of the biodiversity in which it is part and with its participation in the actions of protection of this natural environment. In this scenario, National Parks play a fundamental role through their institutional communication actions. Protagonism also corroborated by the global treaties that Brazil is part of, since they guide these officially protected natural areas that effectively exercise the function of promoting critical-reflexive knowledge. In favor of this perspective, this research investigated the Iguaçu National Park and deepened the scientific approach in the relations between the fields of institutional communication and socioenvironmental sustainability. The research problem is in the understanding of how the institutional communication of this National Park can help in the achievement of its creation objectives, since this area composes a national system of conservation units. The choice of this object of study is validated by its creation history, added to the complexity of current management, which tries to equalize the protection of its ecosystem attributes to the increasing mass tourist visitation. The corpus of analysis was constructed from the following methodological techniques: bibliographic reference, documentary survey, focus group, applied questionnaire and direct observation in the field. The results show that the institutional communication of the Iguaçu National Park influences its visitors, as well as its different actors - employees, subcontractors and the regional population. The activity interferes in different ways, but mainly, when carried out in an institutionalized way, it promotes a better reflection-critical for social-environmental engagement. Despite the history of communicational actions the research observed that the activity is still underdeveloped or underutilized. In this sense, therefore, the study demonstrates the great potential of development, organizational and creative, from the experiences of visitation and the numerous socioenvironmental references inherent to the National Park itself and the surrounding regions.